Factors related to patient propensity to receive adjuvant chemotherapy and outcomes in stage III gastric cancer cases after D2 surgery - Jen-Shi Chen; Chia-Yen Hung; Keng-Hao Liu; Chun-Yi Tsai; Yung-Chia Kuo; Jun-Te Hsu; Wen-Chi Chou (Asian Journal of Surgery, 2019)
Summary: Background: Radical gastrectomy and extended lymph node (D2) dissection followed by adjuvant chemotherapy is the optimal treatment for patients with stage III gastric cancer in Asian population. The clinical factors associated with patient propensity to receive adjuvant chemotherapy and outcomes were analyzed. Methods: In total, 509 patients with stage III gastric cancer who had undergone D2 surgery between 2007 and 2017 at a single medical center in Taiwan were analyzed. The patients' preoperative clinical characteristics relevant to adjuvant chemotherapy adherence were analyzed using multivariate regression. Significant variables were analyzed using recursive partitioning analysis (RPA) for identifying specific patient groups with the lowest and highest probabilities of adjuvant chemotherapy adherence. Results: After surgery, 361 (70.9%) patients in the cohort had received adjuvant chemotherapy. All patients were categorized into five probability groups with adherence to adjuvant chemotherapy according to age, Eastern Cooperative Oncology Group (ECOG) performance status grade, and American Society of Anesthesiologists (ASA) class, which were discovered to be independent factors in the RPA-based probability prediction. In general, adjuvant chemotherapy improved survival across broad categories of stage III gastric cancer patients (overall survival hazard ratio: 0.53–0.75 and disease-free survival hazard ratio: 0.47–0.76). Conclusions: Our study identified that age, ECOG grade, and ASA class were independent clinical factors associated with patient propensity to receive adjuvant chemotherapy in stage III gastric cancer. Knowledge of the clinical factors of patients may help clinicians identify and encourage specific patients to receive the adjuvant chemotherapy. Keywords: Stage III gastric cancer, Adjuvant chemotherapy, Clinical factors, Survival outcome